Effect of multiple freeze-thaw cycles on the stability of positive anti-treponemal serum samples - Marcia Jorge Castejon; Rosemeire Yamashiro; Camila C. Oliveira; Elaine L. Oliveira; Edilene P. R. Silveira; Carmem Aparecida F. Oliveira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Biological samples have long been used in multiple laboratory investigations, and this procedure has been an issue of concern, as the samples are submitted to repeated freeze-thaw cycles, which may affect the results of a particular immunodiagnostic assay, due to the occurrence of physical damage to the antibody of interest. Objective: This study aimed at investigating the impact of successive freeze-thaw cycles on the stability of serum samples stored at -20ºC regarding the reactivity of anti-treponemal antibodies. Methods: At the Immunology Center-Instituto Adolfo Lutz (IAL), the analyzed serum samples analyzed were prepared and established as reference material for anti-treponemal immunodiagnostic assays. Sera stability was evaluated by chemiluminescence assay in samples submitted to 25 successive freeze-thaw cycles, ranging from 6 to 174 cycles. Results: Neither statistically significant effect on the reactivity of anti-treponemal antibodies (p-value > 0.05), nor adverse effect were observed in weakly reactive samples, such as the occurrence of false-negative results. Conclusion: It was shown that 174 freeze-thaw cycles of anti-treponemal sera did not affect the stability and the quality of samples, when evaluated by chemiluminescence assay.